Salvia miltiorrhiza polysaccharide-Mn²⁺-PLGA as an adjuvant in H9N2 vaccine: Immunomodulatory effects in chickens - Yixuan Zhu; Pengfei Gu; Yongzhan Bao; Bowen Song; Jinglu Zhang; Xiao Wang; Wanyu Shi (Poultry Science)
H9N2 is an increasing threat to global poultry production and human health. Vaccination of poultry is a key element of disease control in endemic countries, but the inactivated H9N2 vaccine needs to be used with adjuvants to compensate for its weak immunogenicity. Salvia miltiorrhiza polysaccharide (SMP) and Mn2+ have received extensive attention because of their ability to enhance adaptive immunity and stimulate IFN-β secretion, respectively. Our previous studies had indicated that Mn2+/SMP encapsulated by PLGA (MS-PLGA) can be used as an effective adjuvant for the model antigen (ovalbumin), triggering a potent and durable immune response in mice. Here, we due to confirm the effect of MS-PLGA in chickens. we successfully prepared MS-PLGA-H9N2 and after immunization, it generated stronger specific IgG antibody and higher HI titers, and it also can activate CD4+ and CD8+ T cells in peripheral blood and spleen. Moreover, both concentrations of the serum cytokine IFN-γ (Th1), IL-6 (Th2) and IFN-β are increased, demonstrating Th1/Th2 without bias. To elucidate the regulatory mechanism of MS-PLGA-H9N2, multi-omics analysis and immunofluorescence of the spleen were explored. The GO and KEGG pathways revealed that immune response and defense response were promoted and lymphocytes of spleen were activated. Overall, MS-PLGA-H9N2 has the potential to be clinically induce to induce potent immune responses in chickens.